(untitled) (Research, Society and Development, 2021)
People who use psychoactive substances often have their rights exempted. Psychosocial Rehabilitation is the guideline for the care of the psychosocial model and seeks to integrate the individual into their network and into a broader social context. Objective: To build a Psychosocial Rehabilitation scale for users of psychoactive substances and calculate their content validity. Methods: Methodological study, of constructing items of a scale after integrative review. The scale was submitted to the evaluation of 5 expert judges. Results: 35 articles supported the creation of 33 items of the scale. The items were divided into the domains of Psychosocial Rehabilitation housing, work and income, social network, autonomy and citizenship, and community care. The responses to items are Likert type, 1 to 5. The Content Validity Index of the scale was 0.85 for the pertinence of the items and 0.847 for suitability to the target population. The scale is considered valid for tests with the study population in its final version of 32 items. Final Considerations: The proposed scale is unprecedented and has valid content for the area of alcohol and other drugs. It will contribute to the evaluation and planning of care for users of community mental health services, from the perspective of Psychosocial Rehabilitation.